Produção e caracterização de carvão ativado a partir da borra de café solúvel - Boligon, Jacqueline (2015)
Coffee ground waste is a residue from soluble coffee production, representing about 48% of raw material quantity used in the process. The high quantities cause environmental problems in the industries. A lot of studies have being conducted to aggregate value to this residue, but they are not applied from industries. The objective of this work was produce activated carbon using coffee ground waste, test different activating agents (KOH, K2CO3, mix of FeCl3 e ZnCl2), evaluate the influence of heat treatment, characterize of the activated carbons, realize adsorption test using methylene blue and verify which isotherm model best fits. The precursor material was submitted to thermogravimetric analysis, moisture and ash. Activated carbons were characterized using the Fourier Transform Infrared (FTIR) spectroscopy, methylene blue adsorption, iodine value, textural characterization. Perform adsorption test with higher surface area carbon and verify which isotherm model best fits. The coffee ground waste had 59,17% ± 0,20 moisture, 0,32% ± 0,05 ash and thermal stability after 550ºC (inert atmosphere). FTIR evaluation showed that after chemical activation, carbons had oxidized sites, vibrations could be observed in 3400 cm-1 (stretching OH) e 1050 a 1200 cm-1 (stretching C-O). A peak in 1743 cm-1 suggested ester groups formation in carbon activated with KOH. Carbon activated with KOH exhibit the best performance on tests of iodine value and methylene blue adsorption, while that activated with mix of FeCl3 e ZnCl2 exhibit the worst performance. Carbon activated with K2CO3 showed similar adsorption capacity (iodine value and methylene blue) than commercial one. Methylene blue and iodine value increased after heat treatment; except for that carbon activated with K2CO3. Activating agents had more influence than heat treatment evaluating iodine value and methylene blue adsorption. Chemical activation promoted changes in the textural properties of the obtained carbons, and increased surface area from 3,16 to 30,23 times depending on the activating agent used; it is also noted increase in total pore volume. The activated carbon with KOH showed a higher surface area and total pore volume, followed by that activated with K2CO3, while that activated with mix of FeCl3 and ZnCl2 had the lowest values. All carbons, however, showed a predominance of microproros before and after heat treatment. The thermal treatment caused an increase in the volume of mesopores in the activated carbon with KOH and K2CO3, 2,64 and 5,30 times, respectively. The carbon activated with KOH and heat-treated showed a better fit to the Langmuir isotherm model, and the constant qm, that is the maximum adsorption capacity, was 833,33 mg g-1.